2018
DOI: 10.2343/geochemj.2.0512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydrocarbons in aerosols and investigation of biogenic sources as a carrier of radiocesium isotopes

Abstract: atmosphere. This indirect release of radionuclides is referred to as secondary emission. Secondary emissions may pose a major contamination problem and adversely affect human health over a prolonged period (Igarashi et al., 2015). Moreover, secondary emissions might extend past the contaminated area and delay the return of refugees. However, radiological emergency evaluation protocols have not included a procedure to assess the environmental impact of secondary emissions (IAEA, 2000). Potential sources of seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Based on recent cumulative knowledge, major resuspension aerosols could be supermicron-sized, such as soil dust (Ishizuka et al, 2017;Kinase et al, 2018) and bioaerosols (Kinase et al, 2018;Igarashi et al, 2019b;Kita et al, 2020;Minami et al, 2020;Igarashi, 2021). Lower possibilities of submicron particle involvement, such as that resulting from forest fires (Kinase et al, 2018) and epicuticular wax (Nakagawa et al, 2018), have been reported. Thus, the regional budget considering supermicron aerosols is significantly different from that considering submicron aerosols: faster supermicron deposition rates necessitated higher emission fluxes to sustain the simulated surface concentrations at the observed levels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent cumulative knowledge, major resuspension aerosols could be supermicron-sized, such as soil dust (Ishizuka et al, 2017;Kinase et al, 2018) and bioaerosols (Kinase et al, 2018;Igarashi et al, 2019b;Kita et al, 2020;Minami et al, 2020;Igarashi, 2021). Lower possibilities of submicron particle involvement, such as that resulting from forest fires (Kinase et al, 2018) and epicuticular wax (Nakagawa et al, 2018), have been reported. Thus, the regional budget considering supermicron aerosols is significantly different from that considering submicron aerosols: faster supermicron deposition rates necessitated higher emission fluxes to sustain the simulated surface concentrations at the observed levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since K16 was published, several emission sources of resuspended 137 Cs have been indicated, such as soil dust (Ishizuka et al, 2017;Kinase et al, 2018) and bioaerosols (Kinase et al, 2018;Nakagawa et al, 2018;Igarashi et al, 2019b;Kita et al, 2020;Minami et al, 2020;Igarashi, 2021), but the relative contributions of these sources, the spatiotemporal variations in the associated emission fluxes, and their size distributions are still not well understood. Kita et al (2020) indicated the associations of rain with fungal spore emissions, and Minami et al (2020) estimated the emission flux of 137 Cs associated with bioaerosols; however, the emission flux has not yet been formulated as a function of meteorological or land surface variables.…”
Section: Constraint Of Modeled Deposition Parametersmentioning
confidence: 99%
“…Ochiai et al (2016) also showed that the temporal variations in fine-mode (< 1.1 µm in diameter) and coarse-mode (> 1.1 µm) 137 Cs behaved differently by season, indicating that the major emission sources could be different between winter and summer. Nakagawa et al (2018) conducted size-resolved n-alkane and 137 Cs measurements in similar forest areas and concluded that among biogenic emission sources, epicuticular wax is less likely and bioaerosols such as pollen and fungal spores are more likely. Based on long-term measurements taken in the same forest area, Kinase et al (2018) indicated the association of mineral dust in late spring and bioaerosols in summer and autumn.…”
Section: Introductionmentioning
confidence: 99%
“…Since K16 was published, several emission sources of resuspended 137 Cs have been indicated, such as soil dust (Ishizuka et al, 2017;Kinase et al, 2018) and bioaerosols (Kinase et al, 2018;Nakagawa et al, 2018;Igarashi et al, 2019b;Kita et al, 2020;Minami et al, 2020;Igarashi, 2021), but the relative contributions of these sources, the spatiotemporal variations in the associated emission fluxes, and their size distributions are still not well understood. 2021) evaluated the performance of the K16 model using concentrations and deposition amounts measured at Fukushima sites and found that the seasonal variations in simulated concentrations were opposite to those observed and that the simulated deposition amounts were underestimated by one to two orders of magnitude.…”
Section: Constraint Of Modeled Deposition Parametersmentioning
confidence: 99%